Cross-cultural adaptation and validation of the Kazakh version of American Orthopaedic Foot and Ankle Society Score (AOFAS) questionnaire - Makhmetova, Meruyert; Baktybergen, Kazybek; Raimagambetov, Yerik; Balbossynov, Bagdat; Saginova, Dina (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The AOFAS-AHS questionnaire is used to evaluate the function of the ankle joint. However, its use in the Republic of Kazakhstan is difficult due to the unavailability of the questionnaire in the Kazakh language. This study aimed to translate and culturally adapt the American Orthopaedic Foot and Ankle Society Ankle-Hindfoot Scale (AOFAS-AHS) into Kazakh (AOFAS-KLV) and evaluate its reliability and validity.Methods: 66 Kazakh-speaking patients with ankle and hindfoot pathologies participated. Statistical analyses included descriptive methods for patient characteristics and questionnaire scores, alongside psychometric analyses to assess reliability (internal consistency and test-retest reliability) and construct validity using guidelines from the Consensus-based Standards for the Selection of Health Measurement Instruments (COSMIN).Results: The AOFAS-KLV demonstrated adequate reliability with a Cronbach’s α of 0.724 for the total score. Test-retest reliability was confirmed with intraclass correlation coefficients (ICC) ranging from 0.853 to 0.958. Content validity showed minimal ceiling and floor effects. Construct validity was acceptable, with Spearman’s rank correlations supporting predefined hypotheses. The Bland-Altman analysis indicated no systematic bias.Conclusions: The culturally adapted AOFAS-KLV is a valid and reliable instrument for assessing foot and ankle pathologies in Kazakh patients, contributing to standardized clinical evaluations and long-term patient monitoring in Kazakhstan. Further research should focus on responsiveness and longitudinal validity.